Future smart : managing the game-changing trends that will transform your world - Canton, James (Da Capo Press, a member of the Perseus Books Group, 2015)
"A forecast of the most important game-changing trends-and how to manage and profit from them to improve your life. We live in a time of complex and radical change. Those that are ill-prepared for the seismic shifts set to occur over the next thirty years will be in for a rough ride. From leading global futurist and advisor James Canton, the acclaimed author of The Extreme Future and Technofutures, comes Future Smart: the essential blueprint on what's coming next. It details the key changes-in health and medicine, technology and communication, the global economy, the earth's climate, energy, and business-that every person, company, and government must understand in order to not only adapt accordingly but thrive in the coming decades. Going beyond prediction, Canton shows readers how to get "future-smart" with strategic steps they can take today to navigate tomorrow successfully. "--